2014
DOI: 10.1128/aem.03504-13
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Stereospecific Hydroxylation of Various Steroids at the 16α Position of the D Ring by the Streptomyces griseus Cytochrome P450 CYP154C3

Abstract: c Cytochrome P450 monooxygenases (P450s), which constitute a superfamily of heme-containing proteins, catalyze the direct oxidation of a variety of compounds in a regio-and stereospecific manner; therefore, they are promising catalysts for use in the oxyfunctionalization of chemicals. In the course of our comprehensive substrate screening for all 27 putative P450s encoded by the Streptomyces griseus genome, we found that Escherichia coli cells producing an S. griseus P450 (CYP154C3), which was fused C terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 39 publications
4
42
0
Order By: Relevance
“…Its formation was shown to be catalyzed by membrane‐bound cytochrome P450s in human and rat liver microsomes;50 beyond that, the hydroxylation of testosterone at the 16α‐position is an important step in the formation of estriol in late pregnancy 51, 52. Soluble P450s of Gram‐positive bacteria, such as CYP154C3 from Streptomyces griseus , P450 BM3 (CYP102A1, variant M01 A82W S72I) from Bacillus megaterium , and CYP145C5 from Nocardia farcinica , were reported to selectively hydroxylate testosterone and related steroids at the 16α‐position 8, 53, 54. Crude preparations of the latter enzyme were particularly efficient (as an isolated P450) and achieved TTNs of 500 to 2300 for this reaction 54.…”
Section: Discussionmentioning
confidence: 99%
“…Its formation was shown to be catalyzed by membrane‐bound cytochrome P450s in human and rat liver microsomes;50 beyond that, the hydroxylation of testosterone at the 16α‐position is an important step in the formation of estriol in late pregnancy 51, 52. Soluble P450s of Gram‐positive bacteria, such as CYP154C3 from Streptomyces griseus , P450 BM3 (CYP102A1, variant M01 A82W S72I) from Bacillus megaterium , and CYP145C5 from Nocardia farcinica , were reported to selectively hydroxylate testosterone and related steroids at the 16α‐position 8, 53, 54. Crude preparations of the latter enzyme were particularly efficient (as an isolated P450) and achieved TTNs of 500 to 2300 for this reaction 54.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxylation of testosterone by human CYPsr eviewed by Agematu et al,[43] and Niwa et al,[49] and by the more recently reported human,[50][51][52] and bacterial[44,[53][54][55][56] CYPs is shown. Hydroxylation of testosterone by human CYPsr eviewed by Agematu et al,[43] and Niwa et al,[49] and by the more recently reported human,[50][51][52] and bacterial[44,[53][54][55][56] CYPs is shown.…”
mentioning
confidence: 89%
“…While each P450 behaves differently, streptomycete P450s have been shown to accept redox proteins from other Streptomyces species, 3638 other bacterial genera including putidaredoxin reductase and putidaredoxin from the P450 cam system in Pseudomonas putida 39,40 and flavodoxin reductase and flavodoxin from Escherichia coli , 41,42 and eukaryotes such as the commercially available spinach ferredoxin reductase and ferredoxin. 43,44 Inspired by the one-component systems, Streptomyces P450s have also been engineered into redox self-sufficient enzymes by the fusion of the P450 protein to the reductase domains of P450 RhF 4547 or CYP102D1. 48 Finally, some P450s, are able to utilize H 2 O 2 as a surrogate for the oxygens, electrons, and proton needed to directly generate Cpd 0 from the substrate-bound high-spin ferric P450 (i.e., peroxide shunt or peroxygenation; Fig.…”
Section: Functionmentioning
confidence: 99%